Strategi Pengembangan Sumber Daya Manusia Dalam Upaya Meningkatkan Kinerja Karyawan pada Hotel Syariah Suria City Bandung - Devi Nawang Wulan; Neng Cahya Komala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the face of the growth of the sharia hotel, which is the world's first honest tourism destination, the destruction of camouflaging human resources is the company's principal need, especially in hospitality, when businesses realize that the economic assets of the 21st century are no longer about physical buildings, but rather the intellectual property of human resources. The development of human resources program covers several aspects of its expansion, including the goals, participants, the program, types, and methods used. In its operational management system, the sharia hotel is said to differ from the conventional one. As for the sharia hotel, it is a business of accommodation hotels that provide food and drink and lodging by applying sharia principles and not selecting them. The study uses fieldwork using a qualitative descriptive approach. This research data collection method is direct observation, interview, angket and documentation at the suria city bandung sharia hotel. Based on research, the implementation of the human resource development program at Hotel Syariah Suria City was attended by all employees and was carried out both formally and informally. The methods applied in the program are training methods and educational methods which include several types of training. Then in the analysis of assessing the success of the development program, Hotel Syariah Suria City Bandung measures this by monitoring changes in work and personality as well as employee behavior before and after the program. Meanwhile, in an effort to overcome obstacles such as participants and time, Hotel Syariah Suria City Bandung provides training according to the method of acceptance, and the understanding of employees. And in terms of time, Hotel Syariah Suria City Bandung has established an SOP for employee leave policies.